Fitoterapia e farmacotécnica no Instituto de Medicina do Além - Urias, Tatiane de Souza (2008)
The use of plants to medicinal purposes, for treatment, healing and prevention of diseases is one of the most ancient forms of medical practice of mankind. A significative part of the drugs which are therapeutically used nowadays were discovered through informations obtained from traditional communities that use natural products in their practices of survival and environment manipulation. This work aims to evaluate and to describe the phytotherapeutical and pharmacotechnic aspects in the “Instituto de Medicina do Além” (IMA) and in the “Sítio 13 de Maio”, according to the production of plant raw material, the prescription, production and dispensation of phytomedicines. It also aims to evaluate the toxicity of the main species used in their preparation. All information was obtained through interviews, visits and bibliographic research on the used species. It was observed that the “Barbatimão”, “Jaborandi” and “Sassafrás” presents references on literature about its toxicological activities. It was also observed that is not possible to establish a parallel between the traditional phytotherapy and the phytotherapy developed in IMA because the phytomedicines produced in the Institute are associated to mystic-religious claims. The technical aspects of the pharmaceutical production of IMA do not exhibits too much differences in comparison to conventional techniques, but qualitative aspects can be improved. This work will constitute a source of orientation to IMA managers, warning them about the toxicological potential of some species and its public health risks. Key words: ethnopharmacology, phytotherapy, pharmacotechnic